Deadly Yellowstone secrets - Trumbo, Kari (Love inspired suspense., 2023)
"Someone's hunting bears in Yellowstone National Park--and now Tamala Roth's the next mark. With a killer at her heels, Tamala must trust Ranger Clint Jackson to safeguard her while searching for the poacher. But when a blizzard traps them in with a criminal who will stop at nothing to silence them, survival becomes a dangerous game."--Amazon.